2018
DOI: 10.1186/s12933-018-0671-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced coronary collateralization in type 2 diabetic patients with chronic total occlusion

Abstract: BackgroundThe extent of coronary collateral formation is a primary determinant of the severity of myocardial damage and mortality after coronary artery occlusion. Type 2 diabetes mellitus (T2DM) represents an important risk factor for impaired collateral vessel growth. However, the mechanism of reduced coronary collateralization in type 2 diabetic patients remains unclear.MethodsWith the reference to the recent researches, this review article describes the pathogenic effects of T2DM on collateral development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 96 publications
5
72
1
1
Order By: Relevance
“…Abundant evidence has demonstrated that T2DM exerts a detrimental effect on glucose and lipid metabolism and vascular endothelial function, leading to development and progression of coronary atherosclerosis and unfavorable clinical outcomes [32][33][34][35] . In this study, T2DM was the only independent risk factor for poor coronary collateralization, suggesting that presence of T2DM is correlated negatively with the development of functional collateral arteries 22,23 , and may contribute partially to adverse prognosis of CTO patients 36 . Although presence of a chronic totally occluded lesion has been considered as a prerequisite for spontaneous collateral recruitment, the mechanism of collateral vessel growth is complex in situations where atherosclerosis affects large conductance arteries 37 , and even become more complicated by the presence of T2DM in which multiple biochemical and cellular components are involved 23,38,39 .…”
Section: Discussionmentioning
confidence: 58%
“…Abundant evidence has demonstrated that T2DM exerts a detrimental effect on glucose and lipid metabolism and vascular endothelial function, leading to development and progression of coronary atherosclerosis and unfavorable clinical outcomes [32][33][34][35] . In this study, T2DM was the only independent risk factor for poor coronary collateralization, suggesting that presence of T2DM is correlated negatively with the development of functional collateral arteries 22,23 , and may contribute partially to adverse prognosis of CTO patients 36 . Although presence of a chronic totally occluded lesion has been considered as a prerequisite for spontaneous collateral recruitment, the mechanism of collateral vessel growth is complex in situations where atherosclerosis affects large conductance arteries 37 , and even become more complicated by the presence of T2DM in which multiple biochemical and cellular components are involved 23,38,39 .…”
Section: Discussionmentioning
confidence: 58%
“…11,26,27 DM adversely affects coronary collateral development through multiple cellular mechanisms on arteriogenesis and angiogenesis, and the formation of coronary collaterals in patients with DM and CTO is infl uenced by various clinical, biochemical and angiographic factors. 28 The diabetic pathophysiology promotes an anti-angiogenic process and meanwhile mitigates pro-angiogenic factors in coronary vasculature during ischemia, jointly leading to impaired collateral growth. 28,29 Although the influence of the DM on collateral development is debatable, 11,[30][31][32][33][34] it has been reported that diabetics and prediabetics generally have a poor acute collateral response because of the diffusely impaired endothelial function, [35][36][37] particularly in the presence of active smoking.…”
Section: Discussionmentioning
confidence: 99%
“…28 The diabetic pathophysiology promotes an anti-angiogenic process and meanwhile mitigates pro-angiogenic factors in coronary vasculature during ischemia, jointly leading to impaired collateral growth. 28,29 Although the influence of the DM on collateral development is debatable, 11,[30][31][32][33][34] it has been reported that diabetics and prediabetics generally have a poor acute collateral response because of the diffusely impaired endothelial function, [35][36][37] particularly in the presence of active smoking. 5,38,39 Whereas the DM and prediabetes aggressively induces atherosclerosis and may be more susceptible to infarction; they can also activate some endogenous cardioprotective mechanisms protecting the left ventricular contractile function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations